Establishing a model fish for the Neotropical region: The case of the yellowtail tetra Astyanax altiparanae in advanced biotechnology - Yasui, George Shigueki; Ferreira do Nascimento, Nivaldo; Pereira-Santos, Matheus; Santos Silva, Amanda Pereira dos; Coelho, Geovanna Carla Zacheo; Visintin, José Antônio; Porto-Foresti, Fábio; Okada Nakaghi, Laura Satiko; Vianna, Norberto Castro; Carvalho, Gabriela Braga; Monzani, Paulo Sérgio; López, Lucia Suárez; et al. (Frontiers in Genetics, 2022)
The use of model organisms is important for basic and applied sciences. In fish, several laboratory species are used to develop advanced technologies, such as the zebrafish (Danio rerio), the medaka (Oryzias latipes), and loach species (Misgurnus spp.). However, the application of these exotic species in the Neotropical region is limited due to differences in environmental conditions and phylogenetic distances. This situation emphasizes the establishment of a model organism specifically for the Neotropical region with the development of techniques that may be applicable to other Neotropical fish species. In this work, the previous research efforts are described in order to establish the yellowtail tetra Astyanax altiparanae as a model laboratory species for both laboratory and aquaculture purposes. Over the last decade, starting with artificial fertilization, the yellowtail tetra has become a laboratory organism for advanced biotechnology, such as germ cell transplantation, chromosome set manipulation, and other technologies, with applications in aquaculture and conservation of genetic resources. Nowadays, the yellowtail tetra is considered the most advanced fish regarding fish biotechnology within the Neotropical region. The techniques developed for this species are being used in other related species, especially within the characins class.